The impact of attention to social information on the development of socialization in childhood - Fujioka Toru; Kosaka Hirotaka (Scandinavian Journal of Child and Adolescent Psychiatry and Psychology, 2025)
Socialization and communication are complex processes. It is important to identify the factors related to their development.